Survei Ketepatan Shooting Permainan Sepakbola Pada Pemain Ssb Hatukau U-14 di Desa Batu Merah Kecamatan Sirimau Kota Ambon - Keliata, Samsi Hidayat; Hasbullah, B.; Matitaputty, J. (Peneliti.net, 2025)
This study aims to determine the accuracy of shooting in a soccer game for U-14 SSB Hatukau players in Batu Merah Village, Sirmau District, Ambon City. This type of research is quantitative descriptive research with a survey method. The sample in this study was 30 U-14 SSB Hatukau players. Data were analyzed using descriptive statistics. Based on the results of the study, the overall shooting accuracy on goal was that 3 people (10%) were in the very good category, 7 people (23%) were in the good category, 9 people (30%) were in the sufficient category, 7 people (23%) were in the less category, and 4 people (13%) were in the very less category. Based on the results of data analysis and discussion, it can be concluded that the accuracy of shooting in a soccer game for U-14 SSB Hatukau players in Batu Merah Village, Sirmau District, Ambon City is good.